A heretic's guide to eternity - Burke, Spencer, 1958-; Taylor, Barry, 1951- (San Francisco : Jossey-Bass, 2006)
The general orthodox Christian view of who gets to heaven and who is doomed to hell is based on the notion that we humans have to choose to "opt in" to God's plan for our salvation by baptism, repentance, prayer, and a righteous life. But what if it's the opposite-we are all in, from the moment we are born, no matter when or where we live, and we have to choose to "opt out" in order to be excluded from God's universal grace?
Jesus beyond Christianity -- Grace beyond religion -- Grace and the God factor -- The end of the world as we know it -- Grace held hostage -- Faith remixed: the fine art of bricolage -- Jesus the heretic -- The mystery of God, grace, and salvation -- All we need is grace -- Conclusion: heresy as a way of life.
Includes bibliographical references (p. 229-244) and indexes.
Keywords: Salvation -- Christianity; Future life -- Christianity; Eternity; Postmodernism -- Religious aspects -- Christianity